Neuronal Network Topology Indicates Distinct Recovery Processes after Stroke. (29th July 2020) - Latifi, Shahrzad; Mitchell, Simon; Habibey, Rouhollah; Hosseini, Fouzhan; Donzis, Elissa; Estrada-Sánchez, Ana María; Nejad, H Rezaei; Levine, Michael; Golshani, Peyman; Carmichael, S Thomas
Abstract: Despite substantial recent progress in network neuroscience, the impact of stroke on the distinct features of reorganizing neuronal networks during recovery has not been defined. Using a functional connections-based approach through 2-photon in vivo calcium imaging at the level of single neurons, we demonstrate for the first time the functional connectivity maps during motion and nonmotion states, connection length distribution in functional connectome maps and a pattern of high clustering in motor and premotor cortical networks that is disturbed in stroke and reconstitutes partially in recovery. Stroke disrupts the network topology of connected inhibitory and excitatory neurons with distinct patterns in these 2 cell types and in different cortical areas. These data indicate that premotor cortex displays a distinguished neuron-specific recovery profile after stroke.